The Global Community yearbook of international law and jurisprudence 2014. Volume I - Ziccardi Capaldo, Giuliana; Global Community (New York : Oxford University Press, 2015)
The 2014 edition of 'The Global Community Yearbook' both updates readers on the important work of long-standing international tribunals and introduces readers to more novel topics in international law. This edition includes expert introductory essays by prominent scholars in the realm of international law, on topics as diverse and current as the intervention of the United States and coalition partners in territories under the control of the Islamic State of Iraq and the Levant (ISIL) to the weak area in the institutional and normative framework of the Revised Treaty of Chaguaramas.
Includes bibliographical references.
Description based on online resource; title from home page (viewed on September 9, 2015).
Keywords: International law -- Periodicals; Jurisprudence -- Periodicals